Power, Privilege and Knowledge: the Untenable Promise of Co-production in Mental “Health” - Rose, Diana; Kalathil, Jayasree (Frontiers in Sociology, 2019)
Abstract This paper looks at the historical antecedents of the idea of ‘coproduction’ and gives some concrete examples in the field of mental health. These prior concepts and their concomitant exemplars show that ‘collaboration’ and ‘partnership’ failed because of the continued existence of unspoken power dynamics between professionals, researchers and policy makers and the service users who had been promised ‘partnership’. We then go onto ask whether coproduction is different and heralds a paradigm shift. We articulate the problems at the level of knowledge, particularly the Enlightenment privileging of reason and the individual cognitive subject. This privileging renders inferior those positioned as lacking these attributes, particularly the mad and the racialized mad. We interrogate modern ‘psy’ science and argue that it instantiates white privilege. We then develop an argument that the survivor movement and the emergence of a survivor, or mad knowledge base duplicates this white privilege epistemically, methodologically and in terms of embodied persons themselves. We offer some solutions and describe how we have grappled with these issues in a project aiming to map knowledge production by users, survivors and persons with psychosocial disabilities. It is an unfinished journey. But we conclude that coproduction between researchers and policy makers and those of us positioned as mad, particularly the racicalised mad, cannot happen when the environment is that of the elite, white academy dependant on the legacies of Enlightenment thinking and a continued Eurocentric lens. We seek not to coproduce but to change thinking and supports for psycho-social suffering local to the contexts of peoples lives.